Green synthesis of Phenothiazinium Schiff base and its nano silver complex using egg white as a catalyst under solvent free condition. (2022) - Kannaiyan, Suba; Easwaramoorthy,; Kannan, Karthik; Andal, V.
Abstract: In the current study, an efficient method was developed for the preparation of phenothiazinium Schiff base ligand followed by the attachment to nanosilver mediated by egg white (lysozyme) as a catalyst and reductant under solvent-free conditions. The synthesized Schiff base ligand, nanosilver, and its complex were characterized by UV, IR, XRD, and NMR. Biological studies for Schiff base ligand, nanosilver, and its complex were investigated. The advantages of this method are environmentally benign process; the product can be isolated simply by filtration, simplicity, elimination of solvents, high product yields, and short reaction times. The synthesized compounds were tested for their in vitro antimicrobial activity using the broth dilution method against Staphylococcus aureus (gram-positive) and E. coli (gram-negative) bacteria. From the results the silver nanocomplex exhibits enhanced antibacterial activity which may be due to the interaction of Schiff base and nano Ag on the bacterial cell wall. The silver complex can be utilized in the future for drug delivery and biomedical applications.